The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.3171/jns.1996.84.5.0737
|View full text |Cite
|
Sign up to set email alerts
|

Use of intraoperative ultrasound for localizing tumors and determining the extent of resection: a comparative study with magnetic resonance imaging

Abstract: A prospective study of 70 patients with intraparenchymal brain lesions (36 gliomas and 34 metastases) was performed to evaluate the efficacy of intraoperative ultrasound (IOUS) in localizing and defining the borders of tumors and in assessing the extent of their resection. Eighteen of the 36 glioma patients had no previous therapy. All of these 18 tumors were well localized by IOUS; margins were well defined in 15 and moderately defined in three. The extent of resection was well defined on IOUS in all 18 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
119
0
17

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(140 citation statements)
references
References 29 publications
4
119
0
17
Order By: Relevance
“…[19][20][21][22][23] Few uses of sonography have been shown in pediatric tumors. 24,25 Sonography is highly operatordependent, and proper orientation with respect to the resection cavity can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] Few uses of sonography have been shown in pediatric tumors. 24,25 Sonography is highly operatordependent, and proper orientation with respect to the resection cavity can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tumor segmentation in iUS is more reliable for metastases and some high-grade gliomas, but is poor for low-grade gliomas. 36,37 To this end, we included only segmentation of well-defined boundaries to add confidence in the analysis and minimize bias from segmentation uncertainty. Further, in the low-grade glioma case ͑patient 2͒, we used the high contrast cyst boundary for the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another technique extensively used during neurosurgical procedures is intra-operative Ultrasounds (iUS); in recent years, multiple studies demonstrated their value in tumor detection during surgery, giving to iUS a foreground position in the field of intraoperative imaging [6][7][8][9]. The main point of value of iUS consists in obtaining a real-time scan repeatable as many times as necessary without the cost and the duration of other intraoperative techniques.…”
Section: Introductionmentioning
confidence: 99%